Clinical Pharmacology of Bacteriophage Therapy: A Focus on Multidrug-Resistant Pseudomonas aeruginosa Infections - Dana Holger; Razieh Kebriaei; Taylor Morrisette; Katherine Lev; Jose Alexander; Michael Rybak (MDPI AG, 2021)
Pseudomonas aeruginosa is one of the most common causes of healthcare-associated diseases and is among the top three priority pathogens listed by the World Health Organization (WHO). This Gram-negative pathogen is especially difficult to eradicate because it displays high intrinsic and acquired resistance to many antibiotics. In addition, growing concerns regarding the scarcity of antibiotics against multidrug-resistant (MDR) and extensively drug-resistant (XDR) P. aeruginosa infections necessitate alternative therapies. Bacteriophages, or phages, are viruses that target and infect bacterial cells, and they represent a promising candidate for combatting MDR infections. The aim of this review was to highlight the clinical pharmacology considerations of phage therapy, such as pharmacokinetics, formulation, and dosing, while addressing several challenges associated with phage therapeutics for MDR P. aeruginosa infections. Further studies assessing phage pharmacokinetics and pharmacodynamics will help to guide interested clinicians and phage researchers towards greater success with phage therapy for MDR P. aeruginosa infections.